The Role of Corporate Strategy in Increasing Student Intake Hotel Tourism Business Ciputra University : JEL Classification: I25, M31, L84, D83, M19 - Cen, Christina Felicia; Sutanto, Juan Fiorentino; Hendra , Hendra (Journal La Bisecoman, 2025)
This paper examines the underlying strategic processes relied upon by students regarding decision-making process in selecting the Hospitality and Tourism Business (HTB) course in Ciputra University. The study measures the perceived value, promotional influence, stakeholder dynamics, and institutional attributes that inform the enrolment behaviour through in-depth interviews of current students as participants of a qualitative case study design. The results indicate that students are attracted, not only to the academic material, but also because of that congruence between the institutional identity and the individual goals, especially those goals concerning entrepreneurship, global awareness, and integrated learning. The importance of strategic involvement of stakeholders (i.e. alumni, parents, and industry partners) was identified as a key facilitator and driver of both trust and enrollment performance. For immersive learning environments and experiential resources, professional identity and career readiness were viewed as the main enabling aspects. Such findings support the significance of aligned branding, experiential pedagogy, and stakeholder synergy with higher education strategy. The analysis adds to the body of writing in academic advertising, value co-creation, and identity-based institutional positioning, giving a replicable framework that universities can use to strengthen the competitiveness of differentiation in the active global environment.